2019
DOI: 10.3390/molecules24101888
|View full text |Cite
|
Sign up to set email alerts
|

A Review: The Bioactivities and Pharmacological Applications of Phellinus linteus

Abstract: Phellinus linteus is a popular medicinal mushroom that is widely used in China, Korea, Japan, and other Asian countries. P. linteus comprises various bioactive components, such as polysaccharides, triterpenoids, phenylpropanoids, and furans, and has proven to be an effective therapeutic agent in traditional Chinese medicine for the treatment and the prevention of various diseases. A number of studies have reported that P. linteus possesses many biological activities useful for pharmacological applications, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 86 publications
3
33
0
3
Order By: Relevance
“…Phellinus linteus is a famous medicinal mushroom that is widely used in Korea, Japan, China, and other Asian countries [ 22 ]. The various components including polyphenols, pyrans, polysaccharides, and triterpenoids play a significant role in improving the health condition [ 23 , 24 ]. Above all, Phellinus linteus mycelium (PLM) was used as medicines or healthy foods to treat several diseases such as infections, ulcer, cancer, and diabetes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phellinus linteus is a famous medicinal mushroom that is widely used in Korea, Japan, China, and other Asian countries [ 22 ]. The various components including polyphenols, pyrans, polysaccharides, and triterpenoids play a significant role in improving the health condition [ 23 , 24 ]. Above all, Phellinus linteus mycelium (PLM) was used as medicines or healthy foods to treat several diseases such as infections, ulcer, cancer, and diabetes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sanghuangporus vaninii , a species of Sanghuang, is a traditional medicinal fungus. The fruiting body of S. vaninii can be used as a traditional Chinese medicine for daily health preservation and adjuvant therapy (Chen et al., 2019). However, its safety had not been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al. (2019) found that Sanghuang were mainly rich in polysaccharides, triterpenoids, and polyphenols. We found the aqueous extracts of S. vaninii fruiting body were rich in polysaccharides, nucleotides, and polyphenols (Figure 2), these polyphenols were representative compounds in Sanghuang (Chen et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FBR, a brown rice product, which is fermented with Aspergillus oryzae, also displayed a stronger suppressor activity against colonic carcinogenesis in DSS-treated Apc min mice [21], and Fisher 344 rats [22]. anti-inflammatory, anti-allergic, anti-angiogenic and antioxidant effects [31,32], and also effectively reduced the growth of human colon carcinoma cells [33][34][35]. Curcuma longa has also been used as a traditional herbal medicine due to its antiatherosclerotic, antidiabetic, antimutagenic, anticancer, and antioxidant effects [36].…”
Section: Discussionmentioning
confidence: 99%